CRUSTAL STRUCTURE OF THE OBRUCHEV RISE AS INDICATED BY SEISMIC DATA - Karp B.Y.; Medvedev S.N.; Prokudin V.G.; Malyarenko A.N.; Sedin V.T. (My University, 1988)
The Obruchev Rise is located near the junction of the Kurile-Kamchatka and Aleutian trenches. Continuous seismic profiling (CSP) has identified the structure of the sedimentary cover and the variations in its thickness. Expeditions by our institute in 1983 and 1986 continued the geological and geophysical investigations of the northwestern Obruchev Rise. Reflected-wave seismic studies with radiobuoys, deep seismic sounding and continuous seismic profiling were performed and rocks from the acoustic basement were collected by dredging. The seismic data indicate that the crust of Obruchev Rise is about 13 km thick, in agreement with the figures obtained on profile 8-0. This is greater than the published figure for the Emperor seamounts [11, 12] and less than that for the Shatskiy rise [13]. This fact and the composition of the acoustic basement that we determined confirm the earlier suggestion that Obruchev Rise consists of oceanic crust.